DIPG-45. Radiation induces a robust interferon response in Diffuse Midline Glioma (DMG), improving the potential for combination immunotherapy. (3rd June 2022) - Minns, Hanna E; Padilla, Oscar; Wei, Hong-Jian; Webster-Carrion, Andrea; Tazhibi, Masih; McQuillan, Nicholas; Zhang, Xu; Yeh, Rebecca; Zhang, Zhiguo; Szalontay, Luca; Pavisic, Jovana; Garty, Guy; et al.
Abstract: Diffuse Midline Glioma (DMG), H3K27M altered, confers a dismal survival of 9-15 months and has a non-inflammatory tumor immune microenvironment (TIME). Radiation therapy (RT) is the mainstay treatment for DMG and has been shown in other cancers to recruit an immune component. However, the effect of RT on the DMG TIME has not been explored. In a syngeneic murine model of pontine DMG (PDGFB+, H3.3K27M, p53−/−), mice were treated with single fraction 15Gy RT or sham control, four mice per group. We performed single cell sequencing after CD45 isolation to evaluate the TIME 4 days post RT and compare to untreated tumor (sham control). Unsupervised clustering of 14, 848 CD45+ cells revealed 16 immune cell subsets, most abundantly microglia at 75% of cells, with four subtypes representing a spectrum of homeostatic to activated. Microglia from RT are more concentrated in the activated subtypes with an upregulation of interferon response (i.e. Isg15, Ifit3) compared to untreated tumor with an increase in several interferon pathways using REACTOME. Consistent with RT response, RT treated tumors have increase in cell cycle regulatory genes such as Cdkn1a, across all clusters. In non-resident myeloid cells, compared to untreated tumor, RT is associated with a robust upregulation of interferon response genes in both macrophages (Isg15 Fold Change (FC) 2.30; Ifit1 FC 1.64; Ifit3 FC 2.02; Cxcl10 FC 2.29) and dendritic cells (Isg15 FC 2.67; Ifit1 FC 1.72; Ifit3 FC 2.06; Cxcl10 FC 1.50). We also find differential expression of immune checkpoints in RT-treated versus untreated tumor with decreased expression of Lag3, Tim3 (Havcr2), and Csf1R and increased expression of Cd47, Sirpa and Gitr (Tnfrsf18) post RT. In summary, RT stimulates a pro-inflammatory TIME response and alters immune checkpoints in DMG, highlighting the potential for combining RT and immunotherapy in these tumors.